Antarctic: Persistent Organic Pollutants and Environmental Health in the Region - CORSOLINI, S. (Elsevier, 2011)
The geographic isolation and extreme climate of Antarctica and the Southern Ocean are responsible for both their late discovery by man and the absence of any human impact (towns, industry, and mining), except for the scientific stations. Unfortunately, many studies have demonstrated that even this remote continent and ocean has been reached by ubiquitous, persistent, and toxic contaminants. The main aim of this article is to review critically the data on the presence of these contaminants in Antarctic organisms, in the framework of the interactions between polar regions and the global changes.